Dense gas star formation efficiency and the LHCN (4−3)′/LHCO+(4−3)′ ratio: insights from a statistical study of infrared bright star-forming galaxies - Jiao, Qian; Gao, Yu; Tan, Qinghua; Gao, Yang (Frontiers in Astronomy and Space Sciences, 2023)
We present a statistical study on dense molecular gas tracers of HCN (4−3), HCO + (4−3) lines and molecular tracers of [C I], and CO observations for a sample of 26 infrared bright star-forming (SF) galaxies. We investigate the dependence of dense gas star formation efficiency traced by HCN (4−3), HCO + (4−3) (that is L IR /L HCN (4−3) , and L IR /L HCO + (4−3) ), and luminosity ratio of) which are sensitive to interstellar medium conditions. Our findings show that both L IR /L HCN (4−3) and L IR /L HCO + (4−3) have moderate correlations with L [C I] (2−1) /L CO (1−0) and R [CI] , while L HCN (4−3) /L HCO + (4−3) does not show any significant correlations with any of the [C I]-CO ratios. We compare the L HCN (4−3) /L HCO + (4−3) ratios of AGN and SF galaxies, and find that although the higher L HCN (4−3) /L HCO + (4−3) ratios are mainly found in AGN, the majority of the L HCN (4−3) /L HCO + (4−3) values in SF galaxies are comparable to those in AGN. Based on our findings, it appears that the L HCN (4−3) /L HCO + (4−3) ratio may not be a reliable indicator of the presence of an AGN, although further investigation is needed to confirm this conclusion.